First report of transient urinary retention after bilateral lumbar ESPB in a patient with FBSS: a case report - Li, Jianzhong; Zhang, Afeng; Shu, Tiankun; Qiao, Jun; Duan, Lei (Frontiers in Medicine, 2025)
The erector spinae plane block (ESPB) is a regional anesthesia technique increasingly used in recent years for postoperative analgesia in thoracic, abdominal, spinal, and hip surgeries. The adoption of this method has been encouraged by its technical simplicity and a low rate of complications. To date, no case reports have described transient urinary retention following lumbar ESPB. Here, we present the case of a 64-year-old male admitted after a fall that resulted in a right hip fracture. He had previously undergone L5/S1 posterior lumbar interbody fusion, which was unsuccessful, resulting in failed back surgery syndrome (FBSS). To alleviate preoperative lumbosacral pain, bilateral ultrasound-guided ESPB was performed at the L5 transverse process level at the bedside, with 20 mL of 0.2% ropivacaine administered on each side. The procedure was uneventful. Approximately 1 h after the block, the patient experienced a strong urge to void but was unable to urinate. Bedside bladder ultrasonography revealed marked bladder distension, and catheterization yielded 700 mL of urine. By the following morning, with the return of lumbosacral pain sensation, the patient regained spontaneous voiding without other neurological deficits. No recurrence occurred until discharge. This case suggests that in patients with a history of spinal surgery and altered paraspinal anatomy, ESPB may result in unintended blockade due to aberrant spread of local anesthetic into the epidural space. Consequently, a comprehensive preprocedural assessment of spinal anatomy and improved postoperative monitoring of lumbosacral plexus function are advised to ensure early detection and management of this rare complication.